Attention to online sales: The role of brand image concerns - Markus Dertwinkel-Kalt; Mats Köster (Journal of Economics & Management Strategy, 2021)
We provide a novel intuition for why manufacturers restrict their retailers' ability to resell brand products online. Our approach builds on models of salience-driven attention according to which price disparities across distribution channels guide a consumer's attention toward prices and lower her appreciation for quality. Absent vertical restraints, therefore, one of two salience distortions—a quality or a participation distortion—can arise in equilibrium. We show that, by ruling out both distortions, vertical restraints on online sales can be socially desirable but can also hurt consumers through higher retail prices. We thereby identify a novel trade-off between efficiency and consumer surplus.
Keywords: 330